EFEKTIFITAS ARANG SEKAM PADI DAN AMPAS KELAPA KERING DALAM MENURUNKAN KADAR TIMBAL PADA AIR SUMUR - Riskirana, Rila (JURNAL MEDIA KESEHATAN, 2014)
Lead (Pb) the heavy metals that are dangerous to humans as causing neurological disorders, impaired kidney function, and disorders of the reproductive system. Rice husk charcoal and dried coconut pulp has a porous surface structure so that it has considerable potential as an absorbent. This study aims to determine paddy rice husk and coconut pulp dried in lowering levels of Lead (Pb) in water wells dug. This is true experiments research by using Pre Post Test. This study did 2 treatments that used rice husk rice and dried coconut pulp in the ratio 25 g: 75 g and 75 g: 25 g with 5 repetitions. To determine differences in decreased levels of Pb before and after treatment, Paired T test that shows the value of p = 0.000 <α (0.05) this means that there is a significant difference in the decrease in lead concentrations in water wells dug before and after treatment.